Current perspectives on forest recovery trends in Guanacaste, Costa Rica - Calvo-Alvarado, J.; Jiménez, V.; Calvo-Obando, A.; Castillo, M. (International Forestry Review, 2019)
The main goal of this study was to evaluate whether the trends in the recovery of forest cover in Guanacaste continued during the past decade and to evaluate if the socioeconomic drivers of recovery have been altered. Our analysis found that forest cover in Guanacaste province increased marginally from 48.14% in 2005 to 50.74% in 2012. This implies that the forest recovery process during this period has continued but with a much smaller pace, showing signs of stagnation. The province landscape has changed since the 1970s, when it was dominated by livestock ranching and was the most deforested province with only 23.6% of forest cover. Today Guanacaste is a good example of an economic development forest transition region, with a matrix of land use that is dominated by new forests in different successional stages, which has resulted in great benefits to society given the ecosystem services that this landscape provides.
Artículo. Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, Ministerio del Ambiente, Energía y Minas. Sistema Nacional de Áreas de Conservación, 2019
Keywords: Deforestación; Bosque seco tropical; Cambio de uso de suelo; Bosque secundario; Cobertura forestal; Servicios ecosistémicos; Paisaje; Deforestation; Tropical dry forest; Land use change; Secondary forests; Forest coverage; Ecosystem services; Landscapes; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING